(Re)Defining Clean Hydrogen: From Colors to Emissions. (1st December 2022) - Kusoglu, Ahmet
Abstract : This article discusses the definition of "clean" hydrogen produced by various pathways with a focus on transitioning from color-coded definitions to one that is based on the emissions generated in its creation. Herein, we also discuss the limitations of color-coding by providing a refined critique and assessment. With increasing emphasis on decarbonization efforts and clean energy transition, clean hydrogen's role has been recognized more than ever, from clean energy bills and roadmaps to net-zero scenarios, which necessitates a clear, unambiguous definition for clean hydrogen. This article aims to help stimulate discussions as some colors' associations may fade in favor of carbon intensity of the hydrogen production, in light of recent developments and interests in re-categorizing hydrogen production pathways and reducing associated carbon intensity from a life-cycle perspective.